Influence of Cold Deformation on Carbide Precipitation Kinetics in a Fe-22mn-0.45c Twip Steel - Monsalve-Gonzalez, A; Artigas-Abuin, A (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The carbide precipitation kinetics in a Fe-22Mn-0.45C TWIP steel subjected to three different cold-deformation levels, annealed at various temperatures, were studied. The studied carbides included chemical compositions, morphology, precipitation sites, volume fraction, and size. Manganese carbides were precipitated in a temperature range between 525 and 650◦ C. Volume fraction increased with cold-deformation and decreased with annealing temperature. Carbide size increased with cold-deformation and annealing temperatures up to 625◦ C, suffering a notable reduction at 650◦ C. Precipitation kinetics were described by means of precipitation curves for 0.1% (vol.) of Fe-Mn-carbides. A kinetic model was used, and two stages were found. Complementarily, austenite grain size and microhardness were also measured. With increases in annealing time, microhardness decreased until it reached a nearly constant value, indicating that recrystallization was complete, while, with increases in annealing temperature, grain size increased. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.